The THE CORRELATION BETWEEN TYPES OF QUESTIONS MASTERY AND READING TEXT ABILITY AT FIRST GRADE OF ENGLISH DEPARTMENT INSTUTUT PENDIDIKAN TAPANULI SELATAN IN 2021/2022 ACADEMIC YEAR - Nina Nurbaidah (Pendidikan Sejarah, 2022)
The purposes of this research were to find out : 1) the extent of the students’types of questions mastery at the first grade students of English Department Institut Pendidikan Tapanuli Selatan 2) the extent of students; reading ability at the fisrt grade students of English Department Institut Pendidikan Tapanuli Selatan 3) whether there is a significant correlation between types of questions mastery and reading ability at the fisrt grade students of English Department Institut Pendidikan Tapanuli Selatan. The population of this research was the fisrt grade students of English Department Institut Pendidikan Tapanuli Selatan. The population of this study consisted of 42 students. So, the sample was 42 students. The method of the research is descriptive method. Thus for collecting data, the writer used multiple choice as the instrument. In analyzing the data, the writer use r product moment formula. The result was found that the data calculation or is 0.631. While rtable o,374. It means rxy is higher than rtable. On the other words ther is a significant correlation between students’ types of questions mastery and their reading ability at the first grade students of English Department Institut Pendidikan Tapanuli Selatan 2021/2022 academic year. Therefire the research was accepted. Key words : Types of Questions Mastery, Reading Text Ability